Synthesis and cytotoxic evaluation of some novel diarylamide possessing quinoxalinedione based on sorafenib - Mojtaba Khandan; Sedighe Sadeghian Rizi; Ghadamali Khodarahmi; Farshid Hassanzadeh (Wolters Kluwer Medknow Publications, 2018)
A series of novel sorafenib analogues containing a quinoxalinedione ring and amide linker were synthesized. A total of 9 novel compounds in 6 synthetic steps were synthesized. Briefly, the amino group of p-aminophenol was first protected which then followed by O-arylation with 5-chloro-2-nitroaniline to provide compound d. Reduction of the nitro group of compound d and cyclization of the diamine group of compound e with oxalic acid afforded compound f which on deacetylation yeilded compound g. Then compound g was reacted with different acyl halides to afford the target compounds 1h-1p. Chemical structures of synthesized compounds were confirmed by 1H NMR and FT-IR analysis. All compounds were evaluated at 1, 10, 50 and 100 μM concentrations for their cytotoxicity against HeLa and MCF-7 cancer cell lines. Some of the compounds showed good cytotoxic activity, especially compounds 1i and 1k-1n with the IC50 values of 19, 16, 22, 18, and 16 μM against MCF-7 cell line and 20, 18, 25, 20, and 18 μM against HeLa cell line, respectively.